Analysis of Global Challenges in Contemporary Islamic The Mediating Role of Quiet Quitting in the Relationship Between Employee Engagement and Turnover Intention in Generation Z Employees - Balqis Salma Labibah; Andik Matulessy; Rr. Amanda Pascarini (CV. Bimbingan Belajar Assyfa, 2026)
The high turnover intention among Generation Z employees in Indonesia has become a concern for organizations because it impacts increased recruitment costs, disrupted human resource stability, and decreased productivity. Generation Z tends to prioritize flexibility, meaningful work, and work-life balance. Therefore, when these expectations are not met, employees are potentially disengaged, manifested through quiet quitting behavior. This study aims to analyze the relationship between employee engagement and turnover intention, with quiet quitting as a mediator variable among Generation Z employees in Indonesia. The study used a quantitative approach with a correlational design and a survey method with 213 respondents selected using purposive sampling. The research instruments included the Employee Engagement Scale, the Quiet Quitting Scale, and the Turnover Intention Scale. Data analysis was conducted using Structural Equation Modeling (SEM). The results showed that employee engagement negatively impacted turnover intention and quiet quitting, while quiet quitting positively impacted turnover intention and mediated the relationship between employee engagement and turnover intention.